Central nervous system vasculitis in systemic lupus erythematosus: a case series report in a tertiary referral centre. (November 2017) - Rodrigues, M; Galego, O; Costa, C; Jesus, D; Carvalho, P; Santiago, M; Malcata, A; Inês, L
Central nervous system (CNS) vasculitis (CNS) in systemic erythematosus lupus (SLE) is a rare and challenging diagnosis. We report four cases of CNS vasculitis that occurred 5 to 16 years after the diagnosis of SLE. Magnetic resonance imaging (MRI) detected different features suggestive of CNS vasculitis: enhancement and thickening of the vascular wall, vascular stenosis, ischemic brain lesions and intracerebral haemorrhage unlikely to correspond to other mimic aetiologies. Three patients received combination therapy with glucocorticoids (GC) and cyclophosphamide (CYC). Intravenous human immunoglobulin (IVIG) was administered when the patient had a past history of serious adverse event to CYC or high infectious risk. All patients showed imagiological improvement, at least partially, 5 to 23 days after starting treatment. We discuss the management of CNS in SLE including the role of magnetic resonance imaging (MRI).